If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8h + 20 = 69 Reorder the terms: 20 + 8h = 69 Solving 20 + 8h = 69 Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '-20' to each side of the equation. 20 + -20 + 8h = 69 + -20 Combine like terms: 20 + -20 = 0 0 + 8h = 69 + -20 8h = 69 + -20 Combine like terms: 69 + -20 = 49 8h = 49 Divide each side by '8'. h = 6.125 Simplifying h = 6.125
| 1-6(4-7x)=-23-3x | | 3(2x-5)-4x=5-4(7-x) | | 30=36a+6b+5 | | x/2-1=2x-7 | | 2(x-3)+21=-03 | | 7(x-8)-8(y+4)=80 | | -144/9 | | 30=36a+6b+c | | 27=4x+7(x-4) | | 2+-4+-5n-7+3n= | | 7x-9x+4=x-8+12 | | 2x-5(2x-10)=18 | | 8(8p+4)-8p=-27-3p | | 4g+8g+2g+9g+3g= | | 3x-5y=33-5x | | -16x-3y=12 | | 27w=-3w | | 456c=4 | | -15+5a=6a | | 10+x=5(x)+40 | | W-13.2=10.4 | | f(-6x)=6x^2-4 | | (3n+5)(n-2)-3n(n+1)=6 | | G-72=36 | | -14-63-(-52)= | | 4x-2-4= | | -6-6p+-1= | | -2(-7x+3)+3x=8x-15 | | 27th=-3w | | log^3(3x+8)=log^3(x^2+x) | | 3x-24+x=180 | | 2n^2+2n=4 |